Mahgoub transform and Hyers-Ulam stability of nth order linear differential equations - S. Deepa; S. Bowmiya; A. Ganesh; Vediyappan Govindan; Choonkil Park; Jung Rye Lee (AIMS Mathematics, 2022)
The main aim of this paper is to investigate various types of Hyers-Ulam stability of linear differential equations of $ n^{th} $ order with constant coefficients using the Mahgoub transform method. We also show the Hyers-Ulam constants of these differential equations and give some main results.